Rejuvenation biotechnology: postponing ill-health via comprehensive damage repair - de Grey, Aubrey (Henry Stewart Talks, 2017)
Overview of previous views of treating aging, Aging related damage taxonomy breakdown, Aging maintenance breaking technologies overview, Future interventions that might extend human life span